2008
DOI: 10.1185/030079908x260862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exenatide versus insulin analogues on weight change in subjects with type 2 diabetes: a pooled post-hoc analysis

Abstract: These findings support the use of exenatide as a treatment option in insulin-naïve subjects with type 2 diabetes and who are overweight and sub-optimally controlled by metformin and sulfonylurea. However, these results should be interpreted with caution given the exploratory nature of this post-hoc analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…3 kg at 6 months), and this was at least 5% body weight in ~22% and at least 10% weight loss in 3.2% of patients. In contrast, most insulin-treated subjects (75.9%) had gained weight (mean 3 kg) [31]. …”
Section: Approved and Experimental Peripherally-directed Pharmacotmentioning
confidence: 99%
“…3 kg at 6 months), and this was at least 5% body weight in ~22% and at least 10% weight loss in 3.2% of patients. In contrast, most insulin-treated subjects (75.9%) had gained weight (mean 3 kg) [31]. …”
Section: Approved and Experimental Peripherally-directed Pharmacotmentioning
confidence: 99%
“…Furthermore, cost-effectiveness analysis also showed that exenatide is comparable to insulin glargine, glibenclamide and pioglitazone when combined with metformin. In a post hoc analysis of pooled data from two other studies, the use of exenatide was compared with insulin analogues (either insulin glargine or biphasic insulin aspart) with changes in weight as the main endpoint; the use of exenatide over 6 month period was associated with an average weight loss of 3 kg whilst patients on insulin gained weight [27]. …”
Section: Exenetide Use In the Management Of T2dm And Comparison Wimentioning
confidence: 99%
“…Glass et al48 pooled data from the above two studies,45,47 to analyze the effect of EXE vs insulins (GLA or BIASP) on weight after 6 months of treatment. Patient demographics for those receiving EXE were as follows: N = 532, mean ±SD age 59.4 ±8.8 years, 54.3% males, 87% Caucasians and 8.3% Hispanics, 9.9 ±6.1 years with DM; for those in the INS group, N = 515, 58.2 ±9.3 years, 53% males, 86.6% Caucasians and 7.8% Hispanics, with 9.6 ±6.0 years with DM.…”
Section: Clinical Efficacy and Safetymentioning
confidence: 99%
“…At endpoint, a higher number of patients in the EXE group reported a BMI < 25 kg/m 2 ( P < 0.0001 vs BL and P < 0.0001 vs INS) and a smaller number of patients reported a BMI ≥ 30 kg/m 2 ( P < 0.0001 vs BL and P > 0.0001 vs INS); more patients in the INS group reported a BMI ≥ 30 kg/m 2 vs BL ( P < 0.0001). 48…”
Section: Clinical Efficacy and Safetymentioning
confidence: 99%